Healthy Eating: Meals Without Cooking - Linda B. Bobroff (EDIS, 2016)
This 2-page fact sheet is a major revision featuring a fun word search and a delicious recipe that requires no cooking. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, July 2016.